A microcycle of inflammation following a team handball game - Chatzinikolaou, A.; Christoforidis, C.; Avloniti, A.; Draganidis, D.; Jamurtas, A. Z.; Stampoulis, T.; Ermidis, G.; Sovatzidis, A.; Papassotiriou, I.; Kambas, A.; Fatouros, I. G. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the time-course of performance and inflammatory responses during a simulated 6-day in-season microcycle following a team handball (TH) game. Twenty-four handball players participated in a 1-week control trial and in an experimental trial (TH game participation followed by a 6-day training microcycle). Concentrations of lactate, glucose, glycerol, triglycerides, nonesterified fatty acids (NEFAs), and ammonia were measured pregame and postgame. Heart rate (HR) was monitored during the game. Performance (jumping, speed, agility, line-drill testing, and strength), muscle damage (knee range of motion [ROM], knee extensors/flexors delayed onset muscle soreness [DOMS], and creatine kinase activity [CK]), inflammatory (leukocyte count, C-reactive protein, interleukins 1ß and 6 [IL-1ß and IL-6], soluble vascular adhesion molecule 1 [sVCAM-1], p-selectin, uric acid, cortisol, and testosterone), and oxidative stress (malondialdehyde [MDA], protein carbonyls [PC], reduced [GSH] and oxidized glutathione [GSSG], total antioxidant capacity (TAC), catalase, glutathione peroxidase activity [GPX]) markers were determined pregame, postgame, and daily for 6 consecutive days postgame. The game induced a marked rise of HR (~170 b/min), lactate (~8-fold), glycerol (60%), NEFA (105%), and ammonia (~62%). Performance deteriorated until 24 hours postgame. Knee ROM decreased (3-5%), whereas DOMS and CK increased (3- to 5-fold and 80-100%, respectively) 24 hours postgame. Leukocyte count, IL-1ß, IL-6, cortisol, MDA, PC, and catalase increased only immediately postgame. C-reactive protein and uric acid increased at 24 hours; sVCAM-1, GSSG, and GPX peaked postgame and remained elevated for 24 hours. The GSH declined until 24 hours postgame. Results suggest that a TH game represents a strong metabolic challenge and induces a short-lived and modest inflammatory response that may affect performance for as long as 24 hours postgame.